Pemetaan Perubahan Luasan Mangrove Menggunakan Citra Sentinel-2A Pasca Kematian Mangrove di Denpasar-Bali - Adinegoro, Rowand Danny Sebastian; Putra, I Dewa Nyoman Nurweda; Putra, I Nyoman Giri (Journal of Marine and Aquatic Sciences; Vol 8 No 1 (2022)DO - 10.24843/jmas.2022.v08.i01.p08, 2022)
Province of Bali is one of the mangrove forests distributed in Indonesia, which is spread over three sites, including Tahura Ngruah Rai. The mangrove area in the Tahura, especially in Denpasar city, mangrove forest suffered due to human activities and natural factors. Therefore, there is a need to monitor the distribution of mangrove forests in the area.  Remote sensing is one of the technologies that can be used to control the extent and distribution of mangrove in that area. The aimed of this study was to determined the best band combination on the Sentinel-2A in detecting the mangrove-specific land cover, which was then used to map the extent of mangrove areas after death. The Band combinations tested are the combinations of band 4-3-2, 11-8-4 dan 8-11-2 on the Sentinel-2A. The results indicated that the value of producer accuracy (PA) as well as user accuracy (UA) in the mangrove class with combined band of 4-3-2 (PA= 92.59%, UA= 98.04%), 11-8-4 (PA= 85.19%, UA=88.46%), and 8-11-2 (PA= 71.15%, UA= 84.09%). This study concluded that the band combination of 4-3-2 is able to detect the mangrove better than the band combination of 11-8-4 and 8-11-2 with the total accuracy and an accuracy of the kappa respectively around 91.24% and 91.15%. Mangrove forests of the Tahura Ngura Rai, Denpasar city, had decreased the extent of mangrove forests by 25.58 hectares over a period of four years in 2016 (before incident) until 2020 (after incident).